Alzheimer’s Disease and Type 2 Diabetes Mellitus: The Use of MCT Oil and a Ketogenic Diet - Junpei Takeishi (MDPI AG, 2021)
Recently, type 2 diabetes mellitus (T2DM) has been reported to be strongly associated with Alzheimer’s disease (AD). This is partly due to insulin resistance in the brain. Insulin signaling and the number of insulin receptors may decline in the brain of T2DM patients, resulting in impaired synaptic formation, neuronal plasticity, and mitochondrial metabolism. In AD patients, hypometabolism of glucose in the brain is observed before the onset of symptoms. Amyloid-β accumulation, a main pathology of AD, also relates to impaired insulin action and glucose metabolism, although ketone metabolism is not affected. Therefore, the shift from glucose metabolism to ketone metabolism may be a reasonable pathway for neuronal protection. To promote ketone metabolism, medium-chain triglyceride (MCT) oil and a ketogenic diet could be introduced as an alternative source of energy in the brain of AD patients.